Energetic effects of velocity and stroke rate control in non-expert swimmers - Chollet, D.; Moretto, P.; Pelayo, P.; Sidney, M. (Biomechanics and Medicine in Swimming VII, 1996)
The improving swimmer's skill charncteristics pass from voluntary motor control (where conscious attention is required) to automatic control (where attention is not required but may be called on, leaving conscious mechanisms available for strategic purposes). What happens in the case of the moderately-skilled swimmer, particularly one who is working toward a peak skill level? From an energetic point of view, is swim performance under voluntary control more costly than that under automatic control? Nine moderately-skilled adult swimmers (3 females, 6 males) whose performance time in the 400-m front crawl was 5 min 35 ± 8.5 s participated in 3 test sessions: l) swim velocity (V) and stroke rate (SR) were self-selected by the su~ects; 2) V was imposed; and 3) V and SR were imposed. In each session, heart rate (HR) was recorded and blood lactate concentration (fLD was determined. The principal finding was that although an increased energy cost was expected for the imposed V and SR trials, the two relevant parameters (HR and [L)) showed no increases, and indeed, some significant reductions.